THE ROLE OF SOCIAL PEDAGOGES IN PATRIOTIC EDUCATION OF CHILDREN AND YOUNG PEOPLE - Spivak, Yaroslav (Social work and education, 2018)
The actual problem of patriotic upbringing of children and youth, the formation of their national consciousness and civic attitudes discussed in the article. The special role of patriotic education in the formation of a young person as a citizen is highlighted. The patriotic upbringing in the context of modern socio-pedagogical realities is considered. The crisis situation of the socio-political conditions of the young generation’s existence is emphasized. In modern conditions, the growing role of social pedagogues in the patriotic education of children and youth is noted. The main tasks of social work in this direction, requirements to professional qualities of social pedagogues are defined. The main technologies of social work that can be applied in forming patriotism of children and youth are characterized. The content of social work technologies with families who have suffered from military aggression is revealed. In the article, social work is considered as a significant means of forming patriotism not only children, the younger generation, but also their families. The expediency of development of optimal directions of social and pedagogical activity in patriotic education of children and youth of Ukraine is substantiated. In order to organize the patriotic education of students in educational institutions, recommendations were given to social educators. Summarized the importance of social pedagogue function in cooperation with all participants in the process of patriotic education of children and younger generation. The necessity of state support in this direction is emphasized not only educational establishments, social institutions, social institutions, medical, legal institutions, public organizations, but also necessarily all those who wish to this process. The further research will be focused on the multidimensional activities of social educators for the formation of new young patriots generations to defend the future independence and prosperity of Ukraine.